Global Warming Mitigation through the Local Action of Environmental Education in the Plantation Area of Palm Oil - Rushayati, Siti Badriyah; Hermawan, Rachmad; Meilani, Resti (Universitas Muhammadiyah Surakarta, 2017)
Oil palm is a strategic mainstay product with a crucial role in the national economy, and it can also be carbon sink to mitigate the negative impact of global warming when managed in environmentally friendly manner. Therefore, management and surrounding community need to have an understanding of the environment, and pro-environmental attitude and behaviour. Action research, which aimed at mitigating global warming through the local action of environmental education (EE), was conducted toward oil palm plantation employee and surrounding community. The EE programme was expected to be able to shape understanding and pro-environmental attitude and behaviour in the target group.Â Rapid observation and interview were carried out in collecting data for EE programme development.Â A needs assessment was conducted in developing the EE subject; based on local environmental problems and gap of target groupâs perception of the problems.Â Global warming-related environmental problems found in the location included air temperature increase, drought and difficulty in determining planting season.Â Spatial analysis based on 1989 and 2014 satellite imagery showed a decrease of the water body, tree vegetated land and open areas, and an increase in non-tree vegetated land and built land, accompanied by an increase in areas with higher temperature range.Â Both employees and the community had a good knowledge of the environment, but less in conservation. The environmental education provided for them had been able to increase their perception on environmental conservation. However, repetition and intensive assistance are still needed to strengthen the perception